2021
DOI: 10.1038/s41467-021-27037-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species host range of staphylococcal phages isolated from wastewater

Abstract: The host range of bacteriophages defines their impact on bacterial communities and genome diversity. Here, we characterize 94 novel staphylococcal phages from wastewater and establish their host range on a diversified panel of 117 staphylococci from 29 species. Using this high-resolution phage-bacteria interaction matrix, we unveil a multi-species host range as a dominant trait of the isolated staphylococcal phages. Phage genome sequencing shows this pattern to prevail irrespective of taxonomy. Network analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 108 publications
9
43
0
Order By: Relevance
“…Although the latent period was the same (90 min) in all three tested bacterial strains, the burst size differed substantially between SE16 (92 PFU/cell) and SE14 or SE18 (3 PFU/cell). Other studies have reported S. epidermidis phages with burst sizes ranging from 4.3 PFU/cell to 49.3 PFU/cell [12,32,[38][39][40], of which siphoviruses showed burst sizes between 6.39 PFU/cell and 49.3 PFU/cell. Our study reports a lower and higher burst size than those previously observed.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the latent period was the same (90 min) in all three tested bacterial strains, the burst size differed substantially between SE16 (92 PFU/cell) and SE14 or SE18 (3 PFU/cell). Other studies have reported S. epidermidis phages with burst sizes ranging from 4.3 PFU/cell to 49.3 PFU/cell [12,32,[38][39][40], of which siphoviruses showed burst sizes between 6.39 PFU/cell and 49.3 PFU/cell. Our study reports a lower and higher burst size than those previously observed.…”
Section: Discussionmentioning
confidence: 91%
“…However, due to the limited number of bacterial strains of unknown diversity tested in this study, no broad conclusions on the host range can be extrapolated. In fact, a recent study has shown wide host ranges as the dominant trait among 94 different staphylococcal phage isolates, from both myo-and siphoviral morphology, as well as a temperate and virulent lifestyle [38].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that kayviruses have an extremely broad host range and are capable of lysing up to 90% of S. aureus strains tested ( 8 ) along with numerous non- S. aureus staphylococcal species ( 9 11 ). Furthermore, the cultivation of phages with resistant bacteria and phage breeding has been shown to lead to the accessible selection of new phage variants with a widened host range ( 8 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we have performed a thorough analysis of the interactions between K. pneumoniae and its phages, using a larger phage-host interaction matrix than in previous studies (de Sousa et al, 2020; Townsend et al, 2021; Venturini et al, 2020). All the analyzed phages but one were novel and encompassed different families and undescribed taxonomical entities (Herridge et al, 2020), showing the importance of carrying out more extensive samplings to uncover the phage diversity (Göller et al, 2021; Kauffman et al, 2022; Maffei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a phage infects only a subset of strains of a given bacterial species (de Jonge et al, 2019). However, some phages can infect different bacterial species (Göller et al, 2021; Kauffman et al, 2022) or even distinct genera (Gambino et al, 2020; Hamdi et al, 2017). Available tools can predict phages’ host range with moderately good accuracies at the family and genus levels, but perform worse at lower taxonomical ranks (Coutinho et al, 2021; Villarroel et al, 2016; Young et al, 2020).…”
Section: Introductionmentioning
confidence: 99%